FAMILY CONTRIBUTION IN CHILDREN'S FAITH EDUCATION AMID GADGETS AND SOCIAL MEDIA - Parlaungan Nainggolan; Andar Gunawan Pasaribu (COMPASS: Journal of Education and Counselling, 2025)
This study aims to analyze the contribution of the family in the faith education of children amidst the intensive and increasing use of gadgets and social media. The main questions of this study are: What are the patterns of digital media use by children? What are the digital mediation strategies employed by families? And how do these three aspects—the role of the family, digital mediation, and spiritual content consumption—interact to form the depth of children's faith? The methodology involves a systematic literature review (SLR) to examine the latest research discussing digital parenting, faith formation, and digital religious practices. The results of the study demonstrate that the family holds a fundamental role in faith formation through affective, cognitive, and and practical contributions, which are further strengthened by digital mediation in the form of active mediation, restrictive mediation, and co-use of religious media. Furthermore, the integration of digital spiritual content, as well as proven offline–online hybrid practices, can enrich the process of children's faith education. This research produces a conceptual model that positions the family as the foundation, digital mediation as the connector, and depth of faith as the primary external outcome. This model offers a new perspective that digital media can serve as a space for spiritual formation when directed reflectively and grounded in faith markers.